Structural arrest and dynamic localization in biocolloidal gels. Issue 26 (14th June 2017) - Mahmoudi, N.; Stradner, A.
Abstract : Gels of casein micelles, interacting via an entropic intermediate-ranged depletion attraction, form through arrested spinodal decomposition. Their stiffness increases with time and is connected to their localization length while their structure remains unchanged. Abstract : Casein micelles interacting via an entropic intermediate-ranged depletion attraction exhibit a fluid-to-gel transition due to arrested spinodal decomposition. The bicontinuous networked structure of the gel freezes shortly after formation. We determine the timescales of structural arrest from the build-up of network rigidity after pre-shear rejuvenation, and find that the arrest time as well as the plateau elastic modulus of the gel diverge as a function of the volume fraction and interaction potential. Moreover, we show using scaling from naïve mode coupling theory that their mechanical properties are dictated by their microscopic dynamics rather than their heterogeneous large scale structure.